Asuhan Kebidanan Komprehensif pada Ny. N Umur 26 Tahun G2P1A0 di Puskesmas Sepinggan Kota Balikpapan Aporan Continuity of Care (COC) - Muhdia; Masruroh (Universitas Ngudi Waluyo, 2024)
Maternal and infant mortality in Indonesia remains a major challenge in health care, especially in areas with limited access to medical services. One effective strategy to reduce these rates is the implementation of continuity of care, which includes monitoring from pregnancy, delivery, postpartum period, to postpartum family planning services. This approach ensures that mothers and babies receive comprehensive and continuous care, which in turn has the potential to reduce mortality and complications. Translated with DeepL.com (free version)Mrs. N, a 26-year-old woman, G2P1A0, at Sepinggan Public Health Center, Balikpapan City. The midwifery management approach used includes Varney's method and documentation in the SOAP format. During the antenatal phase, care focused on monitoring maternal and fetal health through routine antenatal visits and educating the mother about danger signs during pregnancy. Delivery care applied principles of respectful maternity care, infection prevention, and clean practices. Postpartum care emphasized maternal recovery, uterine involution monitoring, lactation management, and family planning counseling. Newborn care included cord care, hypothermia prevention, exclusive breastfeeding, and monitoring the baby’s vital signs. The results showed that Mrs. N successfully went through all stages of care without significant complications. The implementation of Continuity of Care ensured integrated and seamless monitoring, providing a sense of safety and comfort for the mother while optimizing maternal and newborn health outcomes. This midwifery care approach plays a crucial role in reducing maternal and infant morbidity and mortality rates. Through comprehensive and continuous care, healthcare professionals can ensure better health outcomes for both mothers and babies. This report highlights the importance of midwifery Continuity of Care as an effective strategy to improve the quality of maternal and newborn health services, and it serves as a reference for further development in midwifery practice. Abstrak Angka kematian ibu dan bayi di Indonesia masih menjadi tantangan besar dalam pelayanan kesehatan, terutama di daerah dengan akses terbatas terhadap layanan medis. Salah satu strategi yang efektif untuk menurunkan angka tersebut adalah penerapan asuhan kebidanan berkelanjutan (Continuity of Care), yang mencakup pemantauan dari kehamilan, persalinan, masa nifas, hingga pelayanan Keluarga Berencana (KB) pasca persalinan. Pendekatan ini memastikan ibu dan bayi mendapatkan layanan yang komprehensif dan berkesinambungan, yang pada akhirnya berpotensi mengurangi angka kematian dan komplikasi. Laporan ini bertujuan untuk memberikan gambaran pelaksanaan Continuity of Care (CoC) pada Ny. N, usia 26 tahun, G2P1A0, di Puskesmas Sepinggan, Kota Balikpapan. Asuhan dilakukan menggunakan pendekatan manajemen kebidanan dengan metode Varney yang terdokumentasi dalam format SOAP. Asuhan meliputi kunjungan antenatal untuk memantau kondisi ibu dan janin, persiapan persalinan, hingga edukasi terkait tanda bahaya kehamilan. Pada tahap persalinan, dilakukan perawatan dengan prinsip asuhan sayang ibu dan pencegahan infeksi. Asuhan masa nifas mencakup pemantauan proses pemulihan ibu, perawatan laktasi, serta edukasi tentang kontrasepsi. Sementara itu, asuhan bayi baru lahir melibatkan pemeriksaan fisik, perawatan tali pusat, pencegahan hipotermia, dan pemberian ASI eksklusif. Hasil asuhan menunjukkan bahwa Ny. N berhasil menjalani proses kehamilan, persalinan, nifas, dan perawatan bayi baru lahir dengan baik tanpa adanya komplikasi. Penerapan Continuity of Care berperan penting dalam memastikan kesehatan ibu dan bayi tetap terjaga serta memberikan rasa aman dan nyaman kepada pasien. Laporan ini diharapkan dapat menjadi referensi untuk meningkatkan kualitas asuhan kebidanan secara berkelanjutan.